Studium magnetických nanostruktur pro spintroniku - Kameš, Jaroslav (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Iontovým naprašováním byly připraveny spin-valve multivrstvy Cu/NiFe/Cu/Co/ (CoOx). Velikost jevu GMR a jeho stabilita v čase byly studovány za pokojové teploty měřením magnetorezistence a magnetooptického Kerrova jevu. Pozornost byla rovněž věnována dosažení opakovatelnosti výroby vzorků, tj. dosažení stejných vlastností pro totožné konfigurace multivrstev.

The Cu/NiFe/Cu/Co/(CoOx) spin-valves have been prepared by the ion-beam sputtering method. Their GMR ratio and the time stability have been investigated by the magnetoresistance and the MOKE measurements at room temperature. The reproducibility of the preparation of the samples have been studied as well, i.e. two identically configurations of the layers should have the same magnetotransport properties.
Study of magnetic nanostructures for spintronics
Keywords: GMR; spin-valve; multivrstvy; spintronika.; GMR; spin-valve; multilayers; spintronics.